1993
DOI: 10.1007/bf01061094
|View full text |Cite
|
Sign up to set email alerts
|

Family pesticide use and childhood brain cancer

Abstract: The relationship between family pesticide use and childhood brain cancer was examined in a case-control study. Telephone interviews were conducted from June 1989 through March 1990 with the natural mothers of 45 childhood brain cancer cases, 85 friend controls, and 108 cancer controls. In comparisons to friend controls, significant positive associations were observed for use of pesticides to control nuisance pests in the home, no-pest-strips in the home, pesticides to control termites, Kwell shampoo, flea coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
86
1
9

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 13 publications
3
86
1
9
Order By: Relevance
“…Few risk factors have been established for childhood cancers other than ionizing radiation (2,3), chemotherapy agents (2), and certain inherited genetic disorders (4,5). Positive associations have been observed in case-control studies between pesticide use in the home or garden and childhood leukemia (6-9) and brain cancer (10,11). Parental occupational exposure to pesticides, determined by occupation from birth certificates or questionnaire, has also been associated with childhood cancer (6,7,(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Few risk factors have been established for childhood cancers other than ionizing radiation (2,3), chemotherapy agents (2), and certain inherited genetic disorders (4,5). Positive associations have been observed in case-control studies between pesticide use in the home or garden and childhood leukemia (6-9) and brain cancer (10,11). Parental occupational exposure to pesticides, determined by occupation from birth certificates or questionnaire, has also been associated with childhood cancer (6,7,(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Several studies used this approach (see Table 1 ). In a study of childhood brain cancer, maternal herbicide use during birth to 6 months was associated with an increased risk, while use during pregnancy was not (Davis et al, 1993 ). The authors suggest that this finding may be due to increased susceptibility of infants to chemical exposures (Davis et al, 1993 ).…”
Section: Exposure Characteristicsmentioning
confidence: 88%
“…These methods allow for the collection of information while both addressing interviewing time constraints and considering participants' attention span. To improve recall, investigators have provided pesticide lists to the study participants either prior to a scheduled telephone interview ( Davis et al, 1993 ) or during the in -person interview ( Donna et al, 1989;Fryzek et al, 1997 ). Pesticide lists during an in -person interview were used as visual cues for all participants for specific pesticide use questions ( Fryzek et al, 1997 ), as memory aids for a subset of participants who were unable to remember substances that had been used ( Donna et al, 1989 ), and as the basis for responses to open -ended questions about pesticide usage (Sanderson et al, 1997 ).…”
Section: Exposure Recallmentioning
confidence: 99%
“…Chadduck et al [16] noticed that the use of heptachlor during pregnancy was associated with gliosarcoma diagnosed in an infant 7 weeks of age. Davis et al [17] found that exposure to carbaryl and diazinon was associated with childhood brain cancer. The role of pesticides in the development of childhood brain cancer has recently been examined in Sweden [18,19], the United States and Canada [20][21][22][23] as well as in the study conducted in seven countries including: the United States (San Francisco, Los Angeles, Seattle), Israel, Italy (Milan), Spain (Valencia), Australia (Sydney), France (Paris) and Canada (Winnipeg) [24] (Table 1).…”
Section: Nervous System Cancersmentioning
confidence: 99%